Applications of the Third-Generation DNA Sequencing Technology to the Detection of Hop Tolerance Genes and Discrimination of Saccharomyces Yeast Strains. (7th April 2022) - Kurniawan, Yohanes Novi; Shinohara, Yuji; Sakai, Hiroaki; Magarifuchi, Tetsuro; Suzuki, Koji
Abstract: To expand the applicability of the third-generation DNA sequencing technologies for the brewing industry, the new experimental protocols for quality control (QC) brewery laboratories have been developed, using the MinION system. Firstly, the hop tolerance genes, horA and horC, were amplified with multiplex PCR, and the PCR amplicons were sequenced by the MinION system. As a result, all of the beer spoilage lactic acid bacteria (LAB) strains carrying horA and/or horC were positively identified. Secondly, STA1, SbKEX2 and GEX1, were evaluated as diagnostic marker genes (DMGs) for discriminating Saccharomyces cerevisiae and S. pastorianus strains that possess essentially indistinguishable nucleotide sequences of the rDNA and internal transcribed spacer (ITS) regions. As a consequence of multiplex PCR specific to STA1, SbKEX2 and GEX1, these DMGs were shown to separate these hard-to-discriminate strains into four groups, namely top-fermenting ale yeast strains ( S. cerevisiae ), bottom-fermenting lager yeast strains ( S. pastorianus ), non-brewing S. cerevisiae wild yeast strains, and S. cerevisiae var. diastaticus . This study also demonstrated that the multiplexed PCR amplicons are independently recognized and correctly identified by the MinION system. Taken together, the newly developed methods using the MinION system are applicable to the identification and discrimination of important brewery microorganisms for microbiological QC. It was also shown that the concurrent applications of the rDNA-sequencing-based species identification and DMG approaches by the MinION system are useful for the breweries that now manufacture both traditional beers and non-traditional beverages. Supplemental data for this article is available online at https://doi.org/10.1080/03610470.2021.1939606 .